Direct experimental evidence of physical origin of electronic phase separation in manganites - Miao, Tian; Deng, Lina; Yang, Wenting; Ni, Jinyang; Zheng, Changlin; Etheridge, Joanne; Wang, Shasha; Liu, Hao; Lin, Hanxuan; Yu, Yang; Shi, Qian; Cai, Peng; et al. (Proceedings of the National Academy of Sciences - PNAS, 2020)
Electronic phase separation in complex oxides is the inhomogeneous spatial distribution of electronic phases, involving length scales much larger than those of structural defects or nonuniform distribution of chemical dopants. While experimental efforts focused on phase separation and established its correlation with nonlinear responses under external stimuli, it remains controversial whether phase separation requires quenched disorder for its realization. Early theory predicted that if perfectly “clean” samples could be grown, both phase separation and nonlinearities would be replaced by a bicritical-like phase diagram. Here, using a layer-by-layer superlattice growth technique we fabricate a fully chemically ordered “tricolor” manganite superlattice, and compare its properties with those of isovalent alloyed manganite films. Remarkably, the fully ordered manganite does not exhibit phase separation, while its presence is pronounced in the alloy. This suggests that chemical-dopinginduced disorder is crucial to stabilize the potentially useful nonlinear responses of manganites, as theory predicted.